Female secondary school and university students dreams and personality factors - Kałużna-Wielobób, Alina (Studia Psychologica: Theoria et praxis, 2012)
The aim of the thesis is to research the connections between “Big Five” personality factors and dreams of female secondary school and university students. The following investigative methods were used: a questionnaire concerning the issue of dreams and NEO Five-Factor Inventory (NEO-FFI) by Costa and McCrae. The group consisted of 397 women. The research resulted in conhrmation of hypotheses about the connections between the content of dreams with four out of hve personality factors: neuroticism, openness, agreeableness and conscientiousness.